Effectiveness of a Brain Protector Combining Murattal Al-Qur'an on Hemodynamics in Patients with Intracerebral Hemorrhage: Case Report - Alfiani, Mahsuna; Chayati, Nur; Purnomo, Sidiq (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Intracerebral hemorrhage (ICH) is a significant global health concern associated with high mortality rates and severe neurological deficits. This study examines the effectiveness of combining citicoline, a neuroprotective agent, with Murattal Al-Qur'an therapy, a non-pharmacological intervention, in managing hemodynamics. Method: A single-case descriptive study was conducted on a 60-year-old male patient diagnosed with hemorrhagic stroke. Results and discussion: Intervention resulted shows that combining citicoline with Murattal Al-Qur'an therapy improved hemodynamic parameters and consciousness levels by protect and stabilizing brain function with citicoline and inducing relaxation and endorphin release with Murattal Al-Qur'an therapy. Conclusion: Integrating citicoline with Murattal Al-Qur'an therapy offers a promising approach to managing hemodynamics and improving outcomes for patients with intracerebral hemorrhage (ICH), particularly in enhancing Glasgow Coma Scale (GCS) scores.